The Discourse Analysis in Video “Why You Don’t Need to Be Exceptional” - Muhammad Egar Virgiansyah (Passage: Journal of English Language and Literature, 2024)
This study explores the usage of language in the motivational video titled “Why You Don’t Need to Be Exceptional”. Specifically, this study aims to investigate some linguistic features such as cohesion system including grammatical cohesion and lexical cohesion as well as theme and rheme including the types and the markedness. This study was conducted by employing a qualitative research approach. This study obtained the data from the transcript of the video that was available on YouTube. The data were analyzed by using two tools of analysis such as Paltridge’s cohesion system (2012) and Eggins’ theme and rheme (2004). The result showed that almost all cohesion system devices were utilized in the content except meronymy. In grammatical cohesion, the dominant cohesion features were conjunction and ellipsis. The use of those devices was useful for making the message more coherent and comprehensible. Regarding lexical cohesion, repetition and synonym were used significantly. It implied that the creator wanted to emphasize particular ideas. Theme and rheme were also investigated in this study and the findings are topical theme became the most frequent type and unmarked theme were more dominant than the marked type. The results indicated that the creator constructed theme and rheme that is easily understandable. Overall, the use of cohesion system and theme and rheme in this motivational video support each other in making the content comprehensible for the audience.